2011
DOI: 10.3354/ame01478
|View full text |Cite
|
Sign up to set email alerts
|

Novel phycodnavirus genes amplified from Canadian freshwater environments

Abstract: Extant and newly designed primers for the polymerase chain reaction (PCR) were used to amplify phycodnavirus DNA polymerase ( polB) gene fragments from numerous samples collected at different times of the year from 3 freshwater environments in Ontario, Canada. Overall, a total of 143 cloned PCR fragments were sequenced and 106 putative phycodnavirus polB gene fragments were identified. Although most of these 106 gene fragments were very closely related (i.e. > 97% identical) to polB sequences from chloroviruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…These viral genotypes may represent viruses infecting other terrestrial hosts, since our annotation was based on translated nucleotide-protein comparisons (i.e., BLASTx) in which average homology to geminiviruses was low. Phycodnaviruses are large double-stranded DNA (dsDNA) viruses that typically infect eukaryotic algae (17,51). Circoviruses, which are circular single-stranded DNA (ssDNA) viruses (48), were large constituents of soil libraries and were less common in freshwater libraries.…”
Section: Discussionmentioning
confidence: 99%
“…These viral genotypes may represent viruses infecting other terrestrial hosts, since our annotation was based on translated nucleotide-protein comparisons (i.e., BLASTx) in which average homology to geminiviruses was low. Phycodnaviruses are large double-stranded DNA (dsDNA) viruses that typically infect eukaryotic algae (17,51). Circoviruses, which are circular single-stranded DNA (ssDNA) viruses (48), were large constituents of soil libraries and were less common in freshwater libraries.…”
Section: Discussionmentioning
confidence: 99%
“…These particular viruses were used in this study because their hosts can be grown in the laboratory and, therefore, titers of infectious viruses can be estimated. Furthermore, close relatives of each of these viruses are known in local freshwaters; CpV-BQ1 was isolated from Ontario waters (Mirza et al, 2015) and DNA polymerase gene sequences closely related to ATCV-1, CVM-1 and CpV-BQ1 have been amplified from the study site (Short et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that different algal viruses such as Prymnesioviruses and Chloroviruses occur in the UTM pond [45], and taxon-specific qPCR methods have already been developed to monitor algal viruses in freshwater environments [24,33,45]. Thus, an obvious and promising next step in this work will be to compare viral production to estimates of virus-mediated mortality.…”
Section: Future Directionsmentioning
confidence: 94%